Two new species of Pestalotiopsis from Southern China - Song, Yu; Geng, Kun; Hyde, Kevin D.; Zhao, Wen-Sheng; Wei, Ji-Guang; Kang, Ji-Chuan; Wang, Yong (Phytotaxa, 2013)
Three Pestalotiopsis isolates were obtained from leaves of Coffea arabica and Rhodomyrtus tomentosa. Among them, two isolates produced versicolorous conidia, and the other produced concolorous conidia. Phylogenetic analysis based on a combination of ITS, β-tubulin and tef1 gene sequence data clearly confirms that they belong to two species and distinguishes them from other species in this genus, with ex-type sequence data in GenBank. On the basis of evidence from morphology and molecular phylogeny they are described as new species, Pestalotiopsis coffeae-arabicae sp. nov. and P. rhodomyrtus sp. nov.